발달지체 영유아에 대한 CBCL 1.5-5 유아행동평가척도-부모용의 요인분석 - 최혜경; Hye Kyung Choi; 하은혜; Eun Hye Ha (한국놀이치료학회지(놀이치료연구), 2015)
본 연구에서는 발달지체 영유아를 대상으로 CBCL 1.5-5 유아행동평가척도의 하위요인 구조를 확인하였다. 서울의 소아정신과 병원과 재활의학센터 2곳에서 발달지체로 판정된 만 1.5-5세의 영유아 245명(남아 184명, 여아 61명)을 대상으로 CBCL 1.5-5 유아행동평가척도, 한국형 Bayley 영유아발달검사 II를 실시하였고, 한국형 아동기 자폐증 평정척도(K-CARS)결과에 따라 자폐진단에 해당하는 아동을 배제하였다. 결과를 보면 발달지체 영유아를 대상으로 CBCL 1.5-5 유아행동평가척도의 기존 7개 문제행동 증후군 척도와 상위요인인 내재화, 외현화 문제행동으로 구성된 2대요인모델에 대해 확인적 요인분석한 결과 적합도가 기준에 부합하지 않았다. 둘째, 발달지체 영유아를 대상으로 99문항으로 탐색적 요인분석을 실시한 결과 최종 53문항이 선정되었으며 충동성, 전반적 발달문제, 불안, 수면문제, 신체증상, 공격행동, 위축과 정서적 반응성 등 8개 요인이 추출되었고 이에 대한 전체 설명력은 42.66%였다. 본 연구를 통해 발달지체의 임상적 평가에 적용할 CBCL1.5-5 유아행동평가척도의 하위요인을 제시한 의의가 있다. This study was conducted with the view to verifying the valuable sub-factor structure of CBCL 1.5-5 for those infants who suffer from developmental delay. The subjects comprised 245 infants(male: 184, female: 61) with developmental delay the in department of Child Psychiatry and Rehabilitation of one general hospital in Seoul. The infants were assessed by means of the K-BSID-Ⅱ and their parents assessed their infants with the K-CARS and Child Behavior Checklist 1.5-5. Those infants who were diagnosed with autism spectrum disorder were excluded by the K-CARS. A confirmatory factor analysis of 2 factor models showed that it was not acceptable for infants with developmental delay. Moreover, exploratory factor analysis showed that 8 sub-factors were extracted. These sub-factors were Impulsiveness, Pervasive Developmental Disorder, Anxiousness, Sleep Problems, Somatic Complaints, Aggressive Behavior, Withdrawn, and Emotionally Reactiveness. These explained 42.66% of the total variances. This study provided a sub-factor structure of CBCL 1.5-5 for infants with developmental delay and the implications of using the CBCL 1.5-5 in infants with developmental delay as a clinical tool.